Long-term outcomes of treatment for unruptured intracranial aneurysms in South Korea: clipping versus coiling. (6th June 2018) - Kim, Young Deok; Bang, Jae Seung; Lee, Si Un; Jeong, Won Joo; Kwon, O-Ki; Ban, Seung Pil; Kim, Tac Keun; Kim, Seung Bin; Oh, Chang Wan
Abstract : Background: The long-term outcomes of endovascular coiling and surgical clipping for the treatment of unruptured intracranial aneurysms are unclear. Methods: We performed a nationwide retrospective cohort study using claims data from the Korean Health Insurance Review and Assessment Service on patients undergoing surgical clipping or endovascular coiling from 2008 to 2014. Inverse probability treatment weighting for average treatment effect on the treated and the multiple imputation method were used to balance covariates and handle missing values. The primary outcome was all-cause mortality at 7 years. Results: We identified 26 411 patients of whom 11 777 underwent surgical clipping and 14 634 underwent endovascular coiling. After adjustment with the use of inverse probability treatment weighting for average treatment effect on the treated, all-cause mortality rates at 7 years were 3.8% in the endovascular coiling group and 3.6% in the surgical clipping group (HR 1.05; 95% CI 0.86 to 1.28; P=0.60, log-rank test). The adjusted probabilities of aneurysm rupture at 7 years were 0.9% after endovascular coiling and 0.7% after surgical clipping (HR 0.9; 95% CI 0.61 to 1.34; P=0.63, log-rank test). The probabilities of retreatment at 7 years after adjustment were 4.9% in the endovascular coiling group and 3.2% in the surgical clipping group (HR 1.52; 95% CI 1.28 to 1.81; P<0.001, log-rank test). Conclusions: All-cause mortality at 7 years was similar between the elective surgical clipping and endovascular coiling groups in patients with unruptured aneurysms who had no history of subarachnoid hemorrhage due to aneurysm rupture.